2021
DOI: 10.3390/microorganisms9051004
|View full text |Cite
|
Sign up to set email alerts
|

Future Risk of Bovine Tuberculosis (Mycobacterium bovis) Breakdown in Cattle Herds 2013–2018: A Dominance Analysis Approach

Abstract: Bovine tuberculosis (bTB) remains a significant endemic pathogen of cattle herds, despite multi-decadal control programmes being in place in several countries. Understanding the risks of future bTB breakdown (BD) and the associated characteristics of herds and index breakdowns could help inform risk categorisation. Such risk categories could then contribute to tailored management and policies. Here, we estimated the future risk of herd BD for the cohort of herds that were derestricted during 2013 in Ireland us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The size of cattle herds has consistently been a risk factor for bTB breakdowns in Ireland and elsewhere when using large national-scale datasets [e.g., (15,16,28,29)], and is therefore unsurprising that a significant relationship was found in the present study. Herds >100 animals, which in the present study represent very large herds, had 19 times higher odds of recent breakdown relative to herds of <30 animals.…”
Section: Herd Size and Dairymentioning
confidence: 64%
See 1 more Smart Citation
“…The size of cattle herds has consistently been a risk factor for bTB breakdowns in Ireland and elsewhere when using large national-scale datasets [e.g., (15,16,28,29)], and is therefore unsurprising that a significant relationship was found in the present study. Herds >100 animals, which in the present study represent very large herds, had 19 times higher odds of recent breakdown relative to herds of <30 animals.…”
Section: Herd Size and Dairymentioning
confidence: 64%
“…Where a farmer selected two options for herd type, only one was used in the model. The response was always taken as the option with the subjective higher bTB risk, given previous research from Ireland [e.g., (2,(15)(16)(17)]. Explicitly, if a farmer picked two different herd types (i.e., a mixed herd), one including a dairy type herd, then that herd was given the indication of "dairy".…”
Section: Discussionmentioning
confidence: 99%
“…However, only a modest proportion of herd-years were coinciding with bTB breakdowns (22% of calves in the dataset were born in a herd during a year with a TB restriction). Furthermore, there is a strong relationship between herd size and bTB risk in Ireland [e.g., ( 37 )], therefore establishing the causative relationship between bTB breakdowns and slaughter rates is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…c) Residual infection poses a future risk to in-contact animals. Many Irish studies have identified herd TB history as a key risk factor for TB presence within a herd [80][81][82][83][84][85][86][87][88][89]. Animals moving following derestriction were 1.91 times more likely to test positive in the following 2 years compared with animals that moved from herds without such a history [90].…”
Section: Other Considerations In Relation To the Performance Of Diagn...mentioning
confidence: 99%